Urolithins and their phase II conjugates cross the blood–brain barrier and exert a stimulus-dependent anti-inflammatory effect on microglial cells by inhibiting NF-κB nuclear translocation - Garay-Mayol, Beatriz (2025)
Neuroinflammation plays a central role in ageing and the progression of neurodegenerative diseases. Epidemiological studies suggest that consuming ellagitannins (ETs)- and ellagic acid (EA)-rich foods like pomegranate or walnuts may confer neuroprotective benefits. However, ETs and EA have low bioavailability and are extensively metabolized by the human gut microbiota into urolithins (Uros), which circulate mainly as glucuronide and sulphate conjugates. This study evaluated the ability of the main colonic Uros (Uro-A, Uro-B, and IsoUro-A), and their respective phase II conjugates, to cross human brain microvascular endothelial cells (HBMECs) as an in vitro model of the blood–brain barrier (BBB), and assessed their anti-(neuro)inflammatory effects on the BBB endothelium and human microglial cells (HMC3) under different inflammatory stimuli. UPLC-qTOF-MS analyses revealed that all Uros and their conjugates crossed the BBB, with Uro-B and its sulphate showing the highest transport efficiency. Moreover, Uros preserved BBB integrity against TNFα-induced damage. In HMC3 cells, all Uros significantly reduced IL-6 secretion, whereas only the free forms decreased IL-8 levels under LPS stimulation. However, no effects were observed in TNFα-stimulated cells, indicating a stimulus-dependent response. Additionally, all Uros prevented NF-κB nuclear translocation in LPS-treated cells, and Uro-A specifically interfered with the canonical MyD88-dependent arm of TLR4 signalling, without broadly inhibiting receptor expression or affecting the TRIF-dependent branch. These findings suggest that consuming ETs and EA-rich foods as precursors of Uros could exert anti-neuroinflammatory activity, potentially preventing or delaying the development of neurodegenerative diseases.